The Shadow of Luther’s Depressions - Borg, Marlies Ter (British Journal of Healthcare and Medical Research, 2025)
Luther suffered from harsh and deep depressions. Some of his own vivid descriptions are quoted. Taking account of the culturally different wording we can in these quotes recognise DSM-5 diagnostic criteria for major depression Sorrow - Depressed mood, most of the day, nearly every day. Self-hate, sinfulness - Feelings of worthlessness or excessive or inappropriate guilt Thoughts of death and hell, - Preoccupation with death In this article I review the theological implications Luther drew from these mood experiences, whereby they became relevant for his followers. He based the interpretation and evaluation of his mood experiences on Biblical writings, notably by David and Solomon. He evaluated his preoccupation with death, his sorrow, sense of sinfulness and worthlessness in a positive way. He included them as essential elements of a generally applicable way to salvation. From his own inability to overcome depression he concluded that man’s fate was predetermined, that he had no freedom of choice between good and evil. Parallel he criticized Papal indulgences, which allowed man to pay his way into heaven. This was central for his break with Catholicism. In four of the 95 theses which triggered the Reformation he formulated the view that sorrow and a sense of sinfulness were to be cultivated. Self-hate was to continue throughout life as an atonement for sin. The lifting of his own personal experiences with major depression up into theological norms implied that his followers were exposed to unnecessary suffering. Erasmus, in debate with Luther, argued that man was free to choose the good as a contribution to happiness or salvation. Erasmus appreciated neither sorrow nor or self-hate. In his In Praise of Folly he made fun of irritable sad men of learning. Erasmus argued for contentment with oneself as essential for achievement. Today both Christian and secular therapists work to alleviate depressed mood or sorrow and boost self-esteem, encouraging patients to work with them to increase their well-being.